The Influence of Price, Product Quality and Service Quality on Consumer Satisfaction in Pt. Mestika Power - Erika Pantun; Rosinta Romauli Situmeang; Tiffany Yunawan (Jurnal Mantik, 2021)
Research done in PT. Mestika Sakti Purpose of the Research is to test and analyze the influence of Price, Product Quality and Service Quality on customer Satisfaction at PT. Mustika Sakti. The research method uses quantitative. The population in this study amounted to 168 of the consumer and the research sample amounted to 118 of the consumer. The sampling technique used is random sampling sampling. The test results show that the partial partial Product Quality has positive and significant effect on customer satisfaction at PT. Mestika Sakti and simultaneous Price, Product Quality, and Service Quality has positive and significant effect on customer Satisfaction at PT. Mustika Sakti